Basic Differentiation Rules


Differentiation is the process of finding a derivative or gradient function.
Given a function $f(x)$, we obtain $f'(x)$ by differentiating with respect to the variable $x$.
There are a number of rules associated with differentiation. These rules can be used to differentiate more complicated functions without having to resort to the sometimes lengthy method of first principles.
Note that the notations, $\dfrac{d}{dx}f(x)$ and $f^{\prime}(x)$ are the same expressions for the derivatives.

Differentiating a constant

$f(x) = c$ then $f^{\prime}(x) = 0$

Example 1

If $f(x)=5$, find $f'(x)$.

\( \begin{align} \displaystyle
f^{\prime}(x) &= 5^{\prime} \\
&= 0 \\
\end{align} \)

Differentiating $x^n$


$f(x) = x^n$ then $f'(x) = nx^{n-1}$

Example 2

If $f(x)=x^7$, find $f^{\prime}(x)$.

\( \begin{align} \displaystyle
f^{\prime}(x) &= (x^7)^{\prime} \\
&= 7x^{7-1} \\
&= 7x^6 \\
\end{align} \)

Constant times a function

$f(x) = cu(x)$ then $f'(x) = cu^{\prime}(x)$
Proof,
\( \begin{align} \displaystyle
f^{\prime}(x) &= \lim_{h \rightarrow 0} \dfrac{f(x+h)-f(x)}{h} \\
&= \lim_{h \rightarrow 0} \dfrac{cu(x+h)-cu(x)}{h} \\
&= \lim_{h \rightarrow 0} c \times \dfrac{u(x+h)-u(x)}{h} \\
&= c \lim_{h \rightarrow 0} \dfrac{u(x+h)-u(x)}{h} \\
&= cu'(x)
\end{align} \)

Example 3

If $f(x)=3x^5$, find $f'(x)$.

\( \begin{align} \displaystyle
f^{\prime}(x) &= (3x^5)^{\prime} \\
&= 3(x^5)^{\prime} \\
&= 3 \times 5x^4 \\
&= 15x^4 \\
\end{align} \)

Addition rule

$f(x) = u(x) + v(x)$ then $f'(x) = u'(x) + v'(x)$
Proof,
\( \begin{align} \displaystyle
f^{\prime}(x) &= \lim_{h \rightarrow 0} \dfrac{f(x+h)-f(x)}{h} \\
&= \lim_{h \rightarrow 0} \dfrac{u(x+h)+v(x+h) – (u(x)+v(x))}{h} \\
&= \lim_{h \rightarrow 0} \Bigg[\dfrac{u(x+h)-u(x)}{h} + \dfrac{v(x+h)-v(x)}{h}\Bigg] \\
&= \lim_{h \rightarrow 0} \dfrac{u(x+h)-u(x)}{h} + \lim_{h \rightarrow 0}\dfrac{v(x+h)-v(x)}{h} \\
&= u^{\prime}(x) + v^{\prime}(x)
\end{align} \)

Example 4

If $f(x)=x^4+x^6$, find $f'(x)$.

\( \begin{align} \displaystyle
f^{\prime}(x) &= (x^4+x^6)^{\prime} \\
&= (x^4)’+(x^6)’ \\
&= 4x^{4-1}+6x^{6-1} \\
&= 4x^3+6x^5 \\
\end{align} \)

Example 5

If $f(x)=\sqrt{x}$, find $f'(x)$.

\( \begin{align} \displaystyle
f(x) &= x^{\frac{1}{2}} \\
f^{\prime}(x) &= \dfrac{1}{2}x^{\frac{1}{2}-1} \\
&= \dfrac{1}{2}x^{-\frac{1}{2}} \\
&= \dfrac{1}{2\sqrt{x}}
\end{align} \)

Example 6

If $f(x)=\dfrac{1}{x^2}$, find $f'(x)$.

\( \begin{align} \displaystyle
f(x) &= x^{-2} \\
f^{\prime}(x) &= -2x^{-2-1} \\
&= -2x^{-3} \\
&= -\dfrac{2}{x^3}
\end{align} \)

Example 7

If $f(x)=\dfrac{1}{\sqrt{x}}$, find $f'(x)$.

\( \begin{align} \displaystyle
f(x) &= x^{-\frac{1}{2}} \\
f^{\prime}(x) &= -\dfrac{1}{2}x^{-\frac{1}{2}-1} \\
&= -\dfrac{1}{2}x^{-\frac{3}{2}} \\
&= -\dfrac{1}{2\sqrt{x^3}}
\end{align} \)

Example 8

If $f(x)=x\sqrt{x}$, find $f'(x)$.

\( \begin{align} \displaystyle
f(x) &= x^{\frac{3}{2}} \\
f^{\prime}(x) &= \dfrac{3}{2}x^{\frac{3}{2}-1} \\
&= \dfrac{3}{2}x^{\frac{1}{2}} \\
&= \dfrac{3}{2}\sqrt{x}
\end{align} \)

Example 9

If $f(x)=\dfrac{2x-1}{x}$, find $f'(x)$.

\( \begin{align} \displaystyle
f(x) &= 2-\dfrac{1}{x} \\
&= 2-x^{-1} \\
f^{\prime}(x) &= x^{-1-1} \\
&= x^{-2} \\
&= \dfrac{1}{x^2}
\end{align} \)


Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorials Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Pythagoras Theorem Quadratic Quadratic Factorise Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Your email address will not be published. Required fields are marked *